IKKβ activates p53 to promote cancer cell adaptation to glutamine deprivation. (November 2018) - Ishak Gabra, Mari; Yang, Ying; Lowman, Xazmin; Reid, Michael; Tran, Thai; Kong, Mei
Abstract One of the hallmarks of cancer is the ability to reprogram cellular metabolism to increase the uptake of necessary nutrients such as glucose and glutamine. Driven by oncogenes, cancer cells have increased glutamine uptake to support their highly proliferative nature. However, as cancer cells continue to replicate and grow, they lose access to vascular tissues and deplete local supply of nutrients and oxygen. We previously showed that many tumor cells situate in a low glutamine microenvironment in vivo, yet the mechanisms of how they are able to adapt to this metabolic stress are still not fully understood. Here, we report that IκB-kinase β (IKKβ) is needed to promote survival and its activation is accompanied by phosphorylation of the metabolic sensor, p53, in response to glutamine deprivation. Knockdown of IKKβ decreases the level of wild-type and mutant p53 phosphorylation and its transcriptional activity, indicating a novel relationship between IKKβ and p53 in mediating cancer cell survival in response to glutamine withdrawal. Phosphopeptide mass spectrometry analysis further reveals that IKKβ phosphorylates p53 on Ser392 to facilitate its activation upon glutamine deprivation, independent of the NF-κB pathway. The results of this study offer an insight into the metabolic reprogramming in cancer cells that is dependent on a previously unidentified IKKβ–p53 signaling axis in response to glutamine depletion. More importantly, this study highlights a new therapeutic strategy for cancer treatment and advances our understanding of adaptive mechanisms that could lead to resistance to current glutamine targeting therapies.